SOUTH AFRICA’S FIRST ANTI-AIRCRAFT GUNS - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Although some useful research has been done onthis topic, it would seem that this has not beenpublished. Quite by chance I have discoveredsome fresh information, which is included inthis offering, which it is hoped will prove auseful interim report.